Molecular Characterization of Epidemic Isolates of Vibrio cholerae O1 by Arbitrarily primed PCR (AP-PCR) - R Ranjbar; MR Pourshafie; N Sadeghifard; A Karami; M Hamidian; M Izadi; M Parzadeh; N Jonaidi (Tehran University of Medical Sciences, 2008)
Background: Epidemic and endemic cholera is a major public health problem for many   countries. Aim of this study was to evaluate AP-PCR for investigation of clonal relatedness among the strains of Vibrio cholerae recovered from an outbreak occurred in different parts of Iran in 2005. Methods: The study was conducted during the cholera outbreak occurred in some of provinces in Iran in summer 2005. Bacterial isolation and identification was carried out according to the standard bacteriological methods. Arbitrarily primed PCR (AP-PCR) used to study the genetic relatedness between the V.cholerae isolates. Results: Thirty-nine isolates of V.cholerae O1 were identified. All isolates belonged to serotype Inaba. AP-PCR could differentiate the isolates into five groups. AP-PCR cluster types 1 and 2 were the most prevalent groups, accounting for 36% and 41%, respectively, of V.cholerae isolates. Conclusion: The most of epidemic strains of V.cholerae O1 isolated in the year 2005 could be attributed to two predominant clusters including AP-PCR cluster types 1 and 2 accounting for more than 77% of isolates. In conclusion, a few epidemic clones were responsible for the apparently epidemic occurrence of cholera in provinces studied.